2022
DOI: 10.1101/2022.02.09.479684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal dynamics of the wild rodent faecal virome

Abstract: Viral discovery studies in wild animals often rely on cross-sectional surveys at a single time point. As a result, our understanding of the temporal stability of wild animal viromes remains poorly resolved. While studies of single host-virus systems indicate that host and environmental factors influence seasonal virus transmission dynamics, comparable insights for whole viral communities in multiple hosts are lacking. Leveraging non-invasive faecal samples from a long-term wild rodent study, we characterised v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Other molecular surveys of viruses in rodents ( Apodemus spp. and Myodes glareolus ) has found that much of the faecal virome is seasonally transient, emphasising the need for longitudinal studies (Raghwani et al ., 2022). However, overall together these studies show that wild rodents commonly have a rich and diverse virome.…”
Section: Discussionmentioning
confidence: 99%
“…Other molecular surveys of viruses in rodents ( Apodemus spp. and Myodes glareolus ) has found that much of the faecal virome is seasonally transient, emphasising the need for longitudinal studies (Raghwani et al ., 2022). However, overall together these studies show that wild rodents commonly have a rich and diverse virome.…”
Section: Discussionmentioning
confidence: 99%
“…This feature could make metagenomic sequencing a suitable tool to screen for zoonotic pathogens in wildlife, and it could facilitate the detection of unexpected or emerging pathogens. Although numerous microbiome‐profiling studies have been performed on humans, such studies performed on wildlife are limited (Egan et al., 2021 ; Firth et al., 2014 ; Ge et al., 2018 ; Raghwani et al., 2022 ; Razzauti et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%